Pengenalan Bioinformatika, Aplikasi dan Database pada Siswa-Siswi SMK Laniang Makassar - Arafah Nurfadillah; Nur Insani Amir; Budyanita Asrun; Laila Syakirah Firani; Julianti Bunga (Yayasan Literasi Sains Indonesia, 2023)
Bioinformatics is one of the fields of science that is currently developing rapidly in society. This is due to the increase in molecular biology research, which has resulted in an unprecedented amount of biological data/information explosion. In its application, bioinformatics uses online software and databases. Community service activities have provided education about Introduction to Bioinformatics, Applications, and Databases to students of SMK Laniang Makassar, Tamalanrea District, Makassar City. This activity was attended by 23 participants from the Computer and Network Engineering (TKJ) department and nursing assistants. This activity aimed to provide knowledge about bioinformatics, databases, and the use of bioinformatics-based applications in various aspects. The activity was carried out for one day, on Wednesday, January 11, 2023, from 09:00 to 13:00 local time. The method used in this activity is by presenting bioinformatics introduction material, databases, and applications related to bioinformatics as well as direct practice using mobile phones, closed with a discussion/question and answer between participants and speakers at the end of the activity. It is known that the result of this service community activity was an increase in student knowledge related to bioinformatics, databases, and bioinformatics applications.